Establishing a legal research agenda for ocean energy. (January 2016) - Wright, Glen; O'Hagan, Anne Marie; de Groot, Jiska; Leroy, Yannick; Soininen, Niko; Salcido, Rachael; Castelos, Montserrat Abad; Jude, Simon; Rochette, Julien; Kerr, Sandy
Abstract: The literature on ocean energy has, to date, largely focussed on technical, environmental, and, increasingly, social and political aspects. Legal and regulatory factors have received far less attention, despite their importance in supporting this new technology and ensuring its sustainable development. Building on the social sciences research agenda developed by the International network for Social Studies of Marine Energy (ISSMER) and published in Energy Policy, a complementary agenda for legal research linked to ocean energy was set out. Key directions for future research structured around the core themes of marine governance: (i) international law; (ii) environmental impacts; (iii) rights and ownership; (iv) consenting processes; and (v) management of marine space and resources were identified. Highlights: Existing research on ocean energy fails to adequately address legal and regulatory issues. Marine governance frameworks play a key role in supporting a sustainable ocean energy industry. An agenda for legal research regarding ocean energy is developed. This agenda provides directions for research and a framework for organising existing studies.